A prospective evaluation of a breast cancer prognosis signature in the observational RASTER study. Issue 4 (4th March 2013) - Drukker, C.A.; Bueno‐de‐Mesquita, J.M.; Retèl, V.P.; van, W.H.; van, H.; Wesseling, J.; Roumen, R.M.H.; Knauer, M.; van 't, L.J.; Sonke, G.S.; Rutgers, E.J.T.; van de, M.J.; et al.
<x xml:space="preserve">Abstract</x> The 70‐gene signature (MammaPrint™) has been developed on retrospective series of breast cancer patients to predict the risk of breast cancer distant metastases. The microarRAy‐prognoSTics‐in‐breast‐cancER (RASTER) study was the first study designed to prospectively evaluate the performance of the 70‐gene signature, which result was available for 427 patients (cT1–3N0M0). Adjuvant systemic treatment decisions were based on the Dutch CBO 2004 guidelines, the 70‐gene signature and doctors' and patients' preferences. Five‐year distant‐recurrence‐free‐interval (DRFI) probabilities were compared between subgroups based on the 70‐gene signature and Adjuvant! Online (AOL) (10‐year survival probability <90% was defined as high‐risk). Median follow‐up was 61.6 months. Fifteen percent (33/219) of the 70‐gene signature low‐risk patients received adjuvant chemotherapy (ACT) versus 81% (169/208) of the 70‐gene signature high‐risk patients. The 5‐year DRFI probabilities for 70‐gene signature low‐risk (n = 219) and high‐risk (n = 208) patients were 97.0% and 91.7%. The 5‐year DRFI probabilities for AOL low‐risk (n = 132) and high‐risk (n = 295) patients were 96.7% and 93.4%. For 70‐gene signature low‐risk–AOL high‐risk patients (n = 124), of whom 76% (n = 94) had not received ACT, 5‐year DRFI was 98.4%. In the AOL high‐risk group, 32% (94/295) less patients would be eligible to receive ACT if the 70‐gene signature was used. In this prospective community‐based observational study, the 5‐year DRFI probabilities confirmed the additional prognostic value of the 70‐gene signature to clinicopathological risk estimations such as AOL. Omission of adjuvant chemotherapy as judged appropriate by doctors and patients and instigated by a low‐risk 70‐gene signature result, appeared not to compromise outcome.